Immunological Studies of Brown Recluse Spider Venom - Elgert, Klaus D. (1974)
Polyacrylamide gel electrophoresis of Loxosceles reclusa venom demonstrated that only one of seven or eight major (plus three or four minor) protein components caused necrosis in guinea pig skin. Sephadex gel filtration separated the venom into three major peaks, the second peak of which contained the dermonecrotic activity. Hyperimmunization of rabbits with increasing doses of venom from L. reclusa produced potent precipitating antisera, and the rabbits became resistant to lesion development. Ouchterlony-type immunodiffusion and immunoelectrophoretic studies revealed six to seven distinct precipitation lines, one of which stained intensely for esterase activity. Immunohistochemical techniques failed to detect any protease, lipase, catalase, acid phosphatase, alkaline phosphatase, or amylase activity in the venom. The spreading activity of recluse spider venom in guinea pig skin was inhibited as much as 71% by antivenom. Venom preincubated with antivenom was unable to incite lesions in guinea pig skin. Passive immunization of guinea pigs 18 h before an injection of venom conferred venom resistance upon the animals. Local injections of antivenom immediately after intradermal injections of venom markedly reduced the dermal lesion. Heparin reduced the local and systemic effects of venom when preincubated with whole venom or when administered systemically before an intradermal injection of venom. Treatment of whole venom with the chelating agent ethylenediaminetetraacetate did not inhibit its necrotic activity. Transfer studies from a 24-h lesion indicated that the necrotic activity was localized and remained active in tissue for at least 24 h but not for 5 days. No lesions developed when high concentrations of venom were intradermally injected into the skin of sacrificed guinea pigs, indicating that an interaction of body constituents and venom is essential for the development of a lesion.